Communication Management Model for Mental Health Prevention and Intervention Program at Telkom University - Maulana, Daris Rohmansyah; Mukhlisiana, Lusy (Bricolage : Jurnal Magister Ilmu Komunikasi, 2026)
This study aims to analyze the management of internal and external communication in Telkom University's mental health prevention and handling program and to formulate a suitable communication management model to enhance the program’s effectiveness. The research is motivated by the high urgency of mental health issues among students and the need for an integrated communication system between internal stakeholders and students as the primary target. Adopting a qualitative case study approach grounded in constructivist theory, this research employs in-depth interviews with key stakeholders—including the Head of Student Affairs, academic advisors, counselors, and students—followed by thematic analysis using Miles and Huberman’s interactive model. The findings reveal that internal communication has been systematically designed by the Directorate of Student Affairs, Career, and Alumni (Ditmawa) through a hierarchical structure involving the Vice Dean II, heads of student affairs, department heads, academic advisors, and counselors. The main challenges in implementation include limited technical human resources (administrative staff) and the low active engagement of academic advisors. External communication employs a multi-channel approach, utilizing social media, MyTelU, iGracias, and other campus programs. However, its effectiveness is still influenced by students' digital literacy and their initiative in accessing information. The proposed communication management model consists of four stages: planning, implementation, monitoring & feedback, and evaluation. This model emphasizes stakeholder collaboration and the optimization of integrated digital channels to effectively reach students. Theoretically, this study strengthens organizational communication perspectives in the context of mental health in higher education. Practically, the model can serve as a strategic reference for building an adaptive and collaborative communication system.